2022
DOI: 10.1126/scirobotics.abo0235
|View full text |Cite
|
Sign up to set email alerts
|

From motor control to team play in simulated humanoid football

Abstract: Learning to combine control at the level of joint torques with longer-term goal-directed behavior is a long-standing challenge for physically embodied artificial agents. Intelligent behavior in the physical world unfolds across multiple spatial and temporal scales: Although movements are ultimately executed at the level of instantaneous muscle tensions or joint torques, they must be selected to serve goals that are defined on much longer time scales and that often involve complex interactions with the environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 90 publications
0
25
0
Order By: Relevance
“…A human dynamic model with 48 DOF was used to visualize and simulate human motion based on experimental motion capture data [30]. Multi-character simulations were also obtained from motion capture data using reinforcement learning [31], [32] and hierarchical reinforcement learning [33]. Data-driven human motion simulations are popular in computer graphics, gaming, and the machine learning community, which can be explained in part by the presence of model-free deep reinforcement learning techniques [19].…”
Section: Related Workmentioning
confidence: 99%
“…A human dynamic model with 48 DOF was used to visualize and simulate human motion based on experimental motion capture data [30]. Multi-character simulations were also obtained from motion capture data using reinforcement learning [31], [32] and hierarchical reinforcement learning [33]. Data-driven human motion simulations are popular in computer graphics, gaming, and the machine learning community, which can be explained in part by the presence of model-free deep reinforcement learning techniques [19].…”
Section: Related Workmentioning
confidence: 99%
“…In this section, we describe a reinforced learning algorithm we use to obtain an approximation of the equilibrium of the Crisis. We treat the entire interaction as a multi-agent reinforcement learning (MARL) problem as it is common in the literature [6,10,12,13], with the assumption that the learning algorithm shall converge to a solution close to the equilibrium. We further verify the quality of the solution by computing its exploitability [9].…”
Section: Learning the Game's Equilibriummentioning
confidence: 99%
“…Pezzotti et al developed MimicBot, a deep RL agent in a Fantasy Football game environment, which achieved excellent performance when RL training techniques were applied after an initial behaviour cloning step [9]. In a more advanced scenario, Liu et al created a framework to train simulated humanoid figures utilizing motion-capture data, and showed that complex behaviours requiring multi-agent coordination could be captured using this approach [4].…”
Section: Related Workmentioning
confidence: 99%